2015
DOI: 10.1097/mbp.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Tp-e/QT ratio and QT dispersion with respect to blood pressure dipping pattern in prehypertension

Abstract: Tp-e, Tp-e/QT, and cQTd are increased in prehypertensives compared with normotensives. Tp-e and Tp-e/QT are associated with the dipping status in prehypertensives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…In our study, heart rate was significantly different among dippers, non-dippers and reverse-dippers in elderly patients with essential hypertension. Moreover, heart rate was lowest in revere-dippers and highest in non-dippers in elderly hypertensive patients, which was inconsistent with previous studies [9,28]. The reverse dipping status is related to the greatest sympathetic activation, which may result in higher heart rate [25].…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…In our study, heart rate was significantly different among dippers, non-dippers and reverse-dippers in elderly patients with essential hypertension. Moreover, heart rate was lowest in revere-dippers and highest in non-dippers in elderly hypertensive patients, which was inconsistent with previous studies [9,28]. The reverse dipping status is related to the greatest sympathetic activation, which may result in higher heart rate [25].…”
Section: Discussioncontrasting
confidence: 67%
“…However, Karaagac et al demonstrated that QTc interval was similar between dippers and non-dippers in patients with metabolic syndrome [8]. Moreover, there was no significant difference among dippers, non-dippers and reverse-dippers in patients with prehypertension in another study [9]. Based on the previous studies, the relationship between QTc and circadian variation of blood pressure remains controversial.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies reported that deteriorated circadian blood pressure variability in prehypertensive patients may be associated with repolarization abnormalities detected by ECG. 15 However, as a marker of depolarization abnormality, the importance of fQRS in prehypertensive patients is not clear. fQRS is a sign of inhomogenous ventricular conduction caused by myocardial scar, ischemia, or fibrosis.…”
Section: Discussionmentioning
confidence: 99%